PLC Simulation Software: Factory I/O with Connected Component Workbench. - Khalil, Zara (linkedin.com, 2022)
Get practice using a simulator PLC from Connected Components Workbench (CCW) software and Factory I/O, a 3D factory simulation that mimics a real-life setting.